PARENTING BEDA GENERASI: POLA ASUH ANAK DALAM PEMBELAJARAN HOLISTIK PADA ZAMAN MILENIAL - Victoria Woen (Sekolah Tinggi Teologi Excelsius, 2022)
Abstract: Child abuse has occurred across borders: brawls, theft, immorality, drugs, pornography, smoking, and the like. The purpose of this newsletter is to study parenting patterns from various generations, the characteristics and functions of their own circle of relatives, and techniques for holistic parenting to be recognized in the millennial era. This study uses a literature study with the results: (1) Generational differences in parenting because generations continue to move so that generational modifications have very large variations in parenting patterns within their own relatives. Now the Alpha era (Z era) born with this generation is growing rapidly. (2) The kinship circle itself is a collection unit in which there may be the presence of different parents, children, and relatives, and have emotional ties and interrelated experiences. (4) Child Parenting Patterns in Holistic Learning in Various Generations of Parenting: Families know parenting, Christ middleÂ noseÂ to parent, the person knows to parent, ability knows parenting, and cyber intelligent know to parent.